2015
DOI: 10.1038/nprot.2015.045
|View full text |Cite
|
Sign up to set email alerts
|

Labeling proteins on live mammalian cells using click chemistry

Abstract: We describe a protocol for the rapid labeling of cell-surface proteins in living mammalian cells using click chemistry. The labeling method is based on strain-promoted alkyne-azide cycloaddition (SPAAC) and strain-promoted inverse-electron-demand Diels-Alder cycloaddition (SPIEDAC) reactions, in which noncanonical amino acids (ncAAs) bearing ring-strained alkynes or alkenes react, respectively, with dyes containing azide or tetrazine groups. To introduce ncAAs site specifically into a protein of interest (POI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
141
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(143 citation statements)
references
References 57 publications
1
141
0
1
Order By: Relevance
“…1,47,48 However, little is known about the impact on protein structure and how any induced structural changes can be used to influence function, in a manner akin to natural PTM events. SPAAC is generally used to attach labels to proteins with no anticipated changes in structure and function but recent studies have indicated it can be used to control enzyme activity, presumably through active site blocking.…”
Section: Resultsmentioning
confidence: 99%
“…1,47,48 However, little is known about the impact on protein structure and how any induced structural changes can be used to influence function, in a manner akin to natural PTM events. SPAAC is generally used to attach labels to proteins with no anticipated changes in structure and function but recent studies have indicated it can be used to control enzyme activity, presumably through active site blocking.…”
Section: Resultsmentioning
confidence: 99%
“…70,90 Nevertheless, our labeling and imaging results as well as studies from others 71 suggest that the ligation product is still relatively stable and dominant, perhaps due to conjugation of the bulky fluorophores. Interestingly, due to the higher reactivity of exo-BCNK with tetrazines than 2’-aTCOK, 48,55 the relative fluorescence labeling efficiency of exo-BCNK after normalization with protein expression level is generally higher than 2’-aTCOK. Therefore, when low protein expression level is desired, exo-BCNK may be used, although the overall fluorescence signal might be dimmer under fluorescence microscopy (Figure S24 and S25).…”
Section: Discussionmentioning
confidence: 99%
“…6,48 For instance, the UAA should be stable for prolonged incubation time in cell culture medium under physiological temperature, and should be highly efficiently incorporated into proteins of interest in mammalian cells. In addition, the organic fluorophores should be carefully selected, as their cellular properties, such as membrane permeability, intracellular distribution, and retention, can affect protein labeling efficiency and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…strained alkenes or alkynes) and fluorophores with corresponding reactivity provides a powerful alternative to conventional fluorophore tagging methods [70][71][72]. However, the approach is technically demanding because it requires sophisticated protocols for the removal of unreacted dye [73]. Ideally the fluorescence of the dye is activated by the coupling reaction; as it is the case for some azido-coumarins and tetrazine-fluorophores [70][71][72].…”
Section: Fluorescence Microscopy and Imagingmentioning
confidence: 98%